2015
DOI: 10.1002/ar.23186
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of the Human Craniofacial Complex

Abstract: Quantifying normal variation and the genetic underpinnings of anatomical structures is one of the main goals of modern morphological studies. However, the extent of genetic contributions to normal variation in craniofacial morphology in humans is still unclear. The current study addresses this gap by investigating the genetic underpinnings of normal craniofacial morphology. The sample under investigation consists of 75 linear and angular measurements spanning the entire craniofacial complex, recorded from late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 75 publications
(113 reference statements)
1
19
0
Order By: Relevance
“…All analyses were performed on the mean value of each sample, using the CS average and the consensus configuration based on Procrustes coordinates. The morphometric analyses were done for the entire skull, and following a previous work (Menéndez et al, ), in three cranial structures in which the skull was divided—face, cranial vault, and cranial base—based on their embryological, developmental, inheritance, and functional characteristics, that allow to consider them as relatively independent units (Cheverud, ; Lieberman, ; Lieberman, Ross, & Ravosa, ; Martínez‐Abadías et al, ; Šešelj, Duren, & Sherwood, ; Sperber, ; but see von Cramon‐Taubadel, ). This allows to compare and evaluate the influence of temperature both on the entire skull and in the mentioned structures, in order to be able to discuss the results with previous ones.…”
Section: Methodsmentioning
confidence: 99%
“…All analyses were performed on the mean value of each sample, using the CS average and the consensus configuration based on Procrustes coordinates. The morphometric analyses were done for the entire skull, and following a previous work (Menéndez et al, ), in three cranial structures in which the skull was divided—face, cranial vault, and cranial base—based on their embryological, developmental, inheritance, and functional characteristics, that allow to consider them as relatively independent units (Cheverud, ; Lieberman, ; Lieberman, Ross, & Ravosa, ; Martínez‐Abadías et al, ; Šešelj, Duren, & Sherwood, ; Sperber, ; but see von Cramon‐Taubadel, ). This allows to compare and evaluate the influence of temperature both on the entire skull and in the mentioned structures, in order to be able to discuss the results with previous ones.…”
Section: Methodsmentioning
confidence: 99%
“…While some scholars argue that the mandible is of not much value in identifying recent human populations (e.g. Humphrey et al, 1999), other recent studies have pointed out that actually, the mandible can reflect population history quite well, as inferred from geographical distance between populations (Nicholson and Harvati, 2006;Harvati and Weaver, 2006), but also from "population continuity" (Galland et al, 2016;Šešelj et al, 2015). Geographical distance might be a fairly robust proxy for inferring restricted gene flow between populations and a good estimate of different climatic conditions.…”
Section: Homo -Journal Of Comparative Human Biology 68 (2017) 329-342mentioning
confidence: 99%
“…Previous studies of global patterns of cranial variation have suggested that certain regions or “modules” of the human cranium are more congruent with neutral genetic data than others, such as the temporal bone hypothesis, cranial vault and basicranum (von Cramon‐Taubadel, ). However, it is generally accepted that the shape of the whole cranial is a reliable indicator of past population history, and the vault generally is a better indicator than facial regions such as the maxilla and zygomatic (Šešelj, Duren, & Sherwood, ; von Cramon‐Taubadel, , ). In the case of the present sample, the basicrania were generally broken or poorly preserved, so the study focuses on the shape of the cranial vault (neurocranium) and the face, which may provide different perspectives on neutral population history as well as potential environmental factors (von Cramon‐Taubadel, Strauss, & Hubbe, ).…”
Section: Methodsmentioning
confidence: 99%
“…The calculation of F ST (or the quantitative genetic equivalent) requires an estimation of heritability and effective population size. Previous studies have shown that human craniofacial shape has a moderate heritability, and different cranial regions vary in their heritabilities (Carson, ; Cole et al, ; Šešelj et al, ). In some cases, the heritability can be assumed to complete (i.e., equal to 1), and the calculated F ST is considered a phenotypic “minimum F ST ”.…”
Section: Methodsmentioning
confidence: 99%